2011
DOI: 10.4049/jimmunol.1002235
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat-Mediated Induction of Platelet-Derived Growth Factor in Astrocytes: Role of Early Growth Response Gene 1

Abstract: HIV-associated neurological disorders (HAND) are estimated to affect almost 60% of HIV infected individuals. HIV-encephalitis (HIVE), the pathological correlate of the most severe form of HAND is often characterized by glial activation, cytokine/chemokine dysregulation, and neuronal damage and loss. However, the severity of HIVE correlates better with glial activation rather than viral load. Using the macaque model, it has been demonstrated that simian immunodeficiency virus encephalitis (SIVE) correlates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Toxicity of HIV Tat on various cells of the CNS has been well documented [14, 15], and it has also been shown that intraventricular injection of the viral protein in rodents results in inflammation, gliosis, apoptosis, and ventricular enlargement [16, 17], with induction of reactive oxygen species (ROS) as a possible mediator of cell damage. Recent reports have implicated induction of ER stress as a major response in various cell types including neurons, astrocytes, and macrophages/microglia in the brains of HIV-positive patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity of HIV Tat on various cells of the CNS has been well documented [14, 15], and it has also been shown that intraventricular injection of the viral protein in rodents results in inflammation, gliosis, apoptosis, and ventricular enlargement [16, 17], with induction of reactive oxygen species (ROS) as a possible mediator of cell damage. Recent reports have implicated induction of ER stress as a major response in various cell types including neurons, astrocytes, and macrophages/microglia in the brains of HIV-positive patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Because HIV Tat is known to induce expression of PDGF-BB in astrocytes (Bethel-Brown et al, 2011;Bethel-Brown et al, 2012) and endothelial cells (Mermis et al, 2011), we sought to examine whether pericytes also responded to HIV Tat by upregulating the expression of PDGF-BB. For this, the pericyte-like cell line (C3H/ 10T1/2) was exposed to HIV Tat101 (200 ng/ml) for varying times (1, 3, 6, 12, and 24 h), and an initial screen was done to identify the RNA levels of different PDGF chains that were expressed by real-time PCR.…”
Section: Tat101-mediated Upregulation Of Pdgf-bb In C3h/10t1/2 Cells mentioning
confidence: 99%
“…Similar to glial activation by inflammatory agents, pericytes have also been shown to be activated in response to lipopolysaccharide (LPS), leading in turn to release of mediators that aid in promoting transcytosis of HIV-1 virus across the BBB (Dohgu and Banks, 2013). Because HIV proteins such as Tat are present in the host despite suppression of virus replication in treated individuals and because Tat is known to induce expression of cerebrovascular permeants such as PDGF (Bethel-Brown et al, 2011;Bethel-Brown et al, 2012), we sought to examine the modulation of PDGF-BB in pericytes exposed to HIV-1 Tat and, subsequently, to examine how this modulation affected pericyte functioning. Herein, cell culture findings were also validated ex vivo in both an HIV-1 transgenic mouse model (Dickie et al, 1991) and sections of the frontal cortex from humans with HIV-encephalitis (HIV-E).…”
Section: Introductionmentioning
confidence: 99%
“…The chemokine can be elaborated not just in response to viral infection but also by exposure to viral proteins, such as tat, which remains present in the CNS despite successful cART[84-86]. HIV tat induces astrocytic CCL2 production [87, 88], as does tat treatment of human microglia [89]. However, the effects of CCL2 may also be protective depending on the kinetics and localization of its expression within the CNS[90].…”
Section: Introductionmentioning
confidence: 99%
“…BBB compromise may also occur as a result of viral proteins[131-135], HIV infection of astrocytes[60, 136, 137], increased CCL2 production [87, 88, 138], and dysregulation of endothelial cell activation/inflammatory markers[139]. These represent additional mechanisms that may facilitate monocyte entry into the CNS of HIV infected individuals.…”
Section: Introductionmentioning
confidence: 99%